Filosofi Keilmuan Lembaga Pendidikan Islam Di Indonesia - Rahmadi; Halimatuzzahra (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This article aims to examine the philosophy of science underpinning three major Islamic educational institutions in Indonesia, namely Islamic boarding schools (pesantren), madrasas, and Islamic higher education institutions (PTKI). The study employs a library research method by analyzing the collective ideas and perspectives of prominent scholars through the lens of the philosophy of science. The findings reveal that the scientific philosophy of pesantren remains predominantly oriented toward tafaqquh fi al-din, emphasizing religious sciences while tending to separate or marginalize ghayr al-shar'iyyah sciences. In madrasas, the dominance of tafaqquh fi al-din has gradually declined with the inclusion of social sciences, natural sciences, and the humanities in the curriculum, although these disciplines are generally implemented within an independent rather than integrated scientific framework. Meanwhile, PTKI has developed diverse models of scientific integration based on different philosophical foundations to bridge the dichotomy between religious and general sciences. Nevertheless, at the practical and institutional levels, the implementation of scientific integration remains an ongoing challenge, requiring stronger epistemological, curricular, and academic efforts to achieve a more comprehensive and sustainable integration of knowledge.This article aims to examine the philosophy of science underpinning three major Islamic educational institutions in Indonesia, namely Islamic boarding schools (pesantren), madrasas, and Islamic higher education institutions (PTKI). The study employs a library research method by analyzing the collective ideas and perspectives of prominent scholars through the lens of the philosophy of science. The findings reveal that the scientific philosophy of pesantren remains predominantly oriented toward tafaqquh fi al-din, emphasizing religious sciences while tending to separate or marginalize ghayr al-shar'iyyah sciences. In madrasas, the dominance of tafaqquh fi al-din has gradually declined with the inclusion of social sciences, natural sciences, and the humanities in the curriculum, although these disciplines are generally implemented within an independent rather than integrated scientific framework. Meanwhile, PTKI has developed diverse models of scientific integration based on different philosophical foundations to bridge the dichotomy between religious and general sciences. Nevertheless, at the practical and institutional levels, the implementation of scientific integration remains an ongoing challenge, requiring stronger epistemological, curricular, and academic efforts to achieve a more comprehensive and sustainable integration of knowledge.